Developing organizations through developing individuals: Malaysian case study - Selamat, Mohamad Hisyam; Abd Wahab, Muhammad Syahir; Mat Samsudin, Mohd Amir (Canadian Center of Science and Education, 2008)
Research has highlighted that organizational development (OD) is a complex issue as it requires the input of employees at all the levels of an organization. However, to obtain this is a challenge for organizations as the basic training and education offered by the organizations and experiences of the individuals on their own and other factors such as fear and ignorance prevent such actions. For this purpose, other elements are also required. This research aims to identify and explain the usage of the elements that can encourage employees to contribute inputs necessary for OD. To achieve this aim, this research developed a conceptual framework based on the elements of understanding organizational roles, internal strengths, formal and informal discussion and rational discourse. To illustrate the application of the framework in a real life setting a case study approach that involved a large manufacturing organization in Malaysia was employed. From this research it was concluded that the future focus for the OD should be towards the development of staff members and creating a suitable organizational culture and infrastructure such that knowledge sharing is promoted.